Self-regulation in early childhood: Analysis of the concept - Breidokienė, Rima; Jusienė, Roma (Psichologija, 2012)
The concept of self-regulation plays one of the major roles in the field of developmental psychology and psychopatology. The importance of self-regulatory capacities for developmental outcomes and behaviors has been well documented in the literature. Contemporary researches on early self-regulation have the roots in the study of W. Mischel and colleagues (1989) who pioneered the studies on the ability of preschool-aged children to delay gratification and exert self-control in the face of strong situational pressures and emotional temptations. Research on the topic of self-regulation in early childhood has increased exponentially in the past 30 years since the first works of W. Mischel and his colleagues. In spite of the growing empirical data, the concept of self-regulation lacks empirical and conceptual clarity, and the developmental picture of self-regulation is fragmented and sometimes inconsistent. Thus, it is very important to make a regular review of the latest research data, integrate it with the existing knowledge and systems, and highlight the main characteristics of self-regulation in early childhood. The aim of the study was to analyze the content and structure of self-regulation and to highlight and discuss the problematic issues of the concept of self-regulation in early childhood. The theoretical discussion of the article covers the historical context of studies on self-regulation in early childhood and the analysis of the constructs conceptually related to self-regulation. The lack of the conceptual clarity of self-regulation is due to multiple perspectives of researchers on self-regulation and the multidimensional nature of this concept. Moreover, different tasks and tests are used to measure the self-regulatory skills of infants and preschool-aged children. The analysis of theoretical and empirical research on early self-regulation has shown that the concept of self-regulation is multidimensional and covers a continuum from effortful and controlled regulation to unconscious and automatic regulation. It is purposeful to conceptualize self-regulation as a unitary construct with multiple levels rather than a construct with multiple definitions. We have revealed several problematic aspects of the concept of self-regulation in early childhood: 1) the multilevel nature of self-regulation structure; 2) a dynamic interplay among self-regulation levels; 3) the differentiation of effortful and reactive control. The methodological challenges while measuring infants’ and preschool-aged children’s self-regulatory capacities as well as implications for future research are also discussed.
Keywords: self-regulation; early childhood; effortful control; reactivity; emotion regulation